Etnobotânica em agrovilas quilombolas de Alcântara, Amazônia Oriental Brasil: uma perspectiva socioambiental quali-quantitativa - Oliveira, Elivaldo Carlos Moreira de (2020)
Ethnobotany has stood out among scientific researches due to the different approaches on plant uses by traditional communities. Among these communities are quilombolas, an ethnicracial group that has developed great knowledge of Brazilian flora since the Colonial Period. In Alcântara there are 157 communities descended from slaves who were abandoned by the masters of the sugar cane and cotton farms in the early 19th century, where several quilombola communities with peculiar characteristics were established and using the resources of this vast ethnic territory communally. These communities remained anonymous until the arrival of the Alcântara Launch Center (CLA), in the early 1980s, when the process of expropriation and compulsory settlement of 312 families began in just seven small villages far from the coast, called by the CLA “agrovilas”. This work aimed to characterize the ethnobotany knowledge of spontaneous native forest species and species cultivated in gardens, farms and gardens in the seven quilombola agrovilas in Alcântara and the relationship of this knowledge with compulsory settlement. The hypothesis is that this process, over three decades, has had negative effects on the traditional knowledge of plants in the quilombola territory. 73 adult and elderly residents were interviewed individually in the seven agrovillages, to whom the free list technique was applied and selected through the snowball method. Phytosociological data from a past study of 12 plots of 1,000 m2 (20 x 50 m) were used in environments of low and medium degradation in the microbasins of the two rivers. The ethnobotanical data were analyzed using univariate statistics (Kruskal-Wallis and Mann-Whitney test) and the Smith Salience and Use Value Indexes. Correlations were made between the phytosociological parameters and the Use Values of the species through the correlation of Spearman. The results demonstrate that the demographic, environmental factors and beliefs are related to the local knowledge of plants; whereas due to the disappearance and reduction of native forest species, exotic fruit grown in backyards play an important role in household food security; whereas forest degradation, despite being related to the loss of spontaneous native species, is a consequence of the compulsory settlement process. Thus, future settlements in other quilombola communities to expand CLA are incompatible with physical reproduction, socioeconomic and cultural status of these communities.